A review on the relationship between computer self-efficacy and attitude toward tele-mental health among school counselors - Lee, Wei Rong; Anuar, Muharram; Zainudin, Zaida Nor; Engku Kamarudin, Engku Mardiah (Human Resources Management Academic Research Society (HRMARS), 2024)
Tele-mental health has emerged as an effective way to extend mental health services to diverse and geographically dispersed populations. However, the success of these programs is not solely dependent on technology, but also on the counsellors’ willingness and readiness to embrace it in their professional practice. This underscores the significant role of counsellors’ attitudes towards technology in executing such initiatives. The present study aimed to explore the relationship between computer self-efficacy and attitudes towards tele-mental health among school counsellors. The methodology applied inclusion and exclusion criteria based on the Ebscohost and Google Scholar databases. The results of this review address that the relationship between computer self-efficacy and attitudes toward tele-mental health among school counsellors highlights that higher confidence in using technology (computer selfefficacy) leads to more positive attitudes toward tele-mental health, as effective training and experience with digital tools make counsellors more willing and adept at integrating telemental health services into their practice. Through the process, ten articles in total were chosen. These results hold important implications for counselling practice, training, and policy formulation, emphasising the necessity of incorporating technology-related training into counselling education programs and providing ongoing support for counsellors in adopting tele-mental health approaches.